Eksklusi dan Inklusi Portal Berita Daring Kasus Perundungan Siswa SMP di Cilacap - Shafira, Dina; Nurhadi, Jatmika; Sudana, Undang (GERAM, 2024)
The case of bullying and mistreatment of several junior high school students against their colleagues went viral on social media. The incident was massively publicized by various media, one of which was online news. This research uses qualitative research with Theo van Leeuwen's discourse analysis theory approach. The data taken from this study are words, phrases, and clauses related to van Leeuwen's exclusion and inclusion strategies in the discourse of bullying news on Detik.com, CNN Indonesia, Liputan6.com, and Tribun Jateng media. The result is that the nominalization exclusion strategy is found in one news discourse text. Furthermore, inclusion strategies in the form of differentiation-indifference, objectivation-abstraction, nomination-categorization, nomination-identification, and assimilation-individualization are found in four news discourse texts, and association-dissociation is found in two news discourse texts. The exclusion strategy in the news discourse texts functions as the removal of actors who bullied junior high school students in Cilacap, Central Java. However, the use of inclusion strategy is more featured in the news discourse texts.